Bacillus altitudinis‐Stabilized Multifarious Copper Nanoparticles Prevent Bacterial Fruit Blotch in Watermelon (Citrullus lanatus L.): Direct Pathogen Inhibition, In Planta Particles Accumulation, and Host Stomatal Immunity Modulation. Issue 15 (4th January 2023) - Noman, Muhammad; Ahmed, Temoor; White, Jason C.; Nazir, Muhammad Mudassir; Azizullah,; Li, Dayong; Song, Fengming
Abstract: The nano‐enabled crop protecting agents have been emerging as a cost‐effective, eco‐friendly, and sustainable alternative to conventional chemical pesticides. Here, the antibacterial activity and disease‐suppressive potential of biogenic copper nanoparticles (bio‐CuNPs) against bacterial fruit blotch (BFB), caused by Acidovorax citrulli ( Ac ), in watermelon ( Citrullus lanatus L.) is discussed. CuNPs are extracellularly biosynthesized using a locally isolated bacterial strain Bacillus altitudinis WM‐2/2, and have spherical shapes of 29.11–78.56 nm. Various metabolites, such as alcoholic compounds, carboxylic acids, alkenes, aromatic amines, and halo compounds, stabilize bio‐CuNPs. Foliar application of bio‐CuNPs increases the Cu accumulation in shoots/roots (66%/27%), and promotes the growth performance of watermelon plants by improving fresh/dry weight (36%/39%), through triggering various imperative physiological and biochemical processes. Importantly, bio‐CuNPs at 100 µg mL −1 significantly suppress watermelon BFB through balancing reactive oxygen species system, improving photosynthesis capacity, and modulating stomatal immunity. Bio‐CuNPs show obvious antibacterial activity against Ac by inducing oxidative stress, biofilm inhibition, and cellular integrity disruption. These findings demonstrate that bio‐CuNPs can suppress watermelon BFB through direct antibacterial activity and induction of active immune response in watermelon plants, and highlight the value of this approach as a powerful tool to increase agricultural production and alleviate food insecurity. Abstract : Biogenic copper nanoparticles suppress bacterial fruit blotch through antibacterial activity and boosting of immune response in watermelon, providing a novel nano‐enabled strategy for sustainable crop disease management.